Developing a Patient-Centered mHealth App: A Tool for Adolescents With Type 1 Diabetes and Their Parents - Holtz, Bree E; Murray, Katharine M; Hershey, Denise D; Dunneback, Julie K; Cotten, Shelia R; Holmstrom, Amanda J; Vyas, Arpita; Kaiser, Molly K; Wood, Michael A (JMIR Publications, 2017)
BackgroundType 1 diabetes (T1D) afflicts approximately 154,000 people under 20 years of age. Three-quarters of adolescents are not achieving glycosylated hemoglobin (HbA1c) targets, which leads to negative health outcomes. Mobile health (mHealth), the use of technology in health, has been used successfully to improve health in many chronic conditions, including diabetes. ObjectiveThe purpose of this study was to use patient-centered research methods to inform and improve the design and functionality of our T1D app, MyT1DHero, and to provide insight for others who are designing a health app for adolescents and parents. MethodsThis study included data from focus groups with participants recruited from the Juvenile Diabetes Research Foundation (JDRF) southeast Michigan's family network. All data collected during the sessions were audio-recorded, transcribed, and coded. ResultsFour key themes were identified: (1) diabetes is unpredictable, (2) negative and frustrated communication, (3) motivations to use an app, and (4) feedback specific to our app. ConclusionsA patient-centered approach was used to assist in the development of an app for adolescents with T1D. Participants were satisfied with overall app design; customization, interactivity, and tangible rewards were identified as being necessary for continued use. Participants believed the app would help improve the communication between parents and adolescents. Many apps developed in the health context have not used a patient-centered design method or have seen vast improvements in health. This paper offers suggestions to others seeking to develop apps for adolescents and their parents.